Relationship between frequency of eating and cardiovascular disease mortality in U.S. adults: the NHANES III follow-up study - Chen, Hsin-Jen; Wang, Youfa; Cheskin, Lawrence J. (Annals of epidemiology, 2016)
This study examined longitudinal relationship between baseline daily eating frequency and all-cause and cardiovascular disease (CVD) mortality among U.S. adults. The Third National Health and Nutrition Examination Survey (1988–1992) participants were followed through 2006. Nonpregnant adults >17 years old (n = 6884) whose dietary recall was of good quality and had fasted at least 8 hours before physical examinations were eligible for this analysis. Frequency of eating was derived from 24-hour dietary recalls. Main outcomes included all-cause and CVD mortality during follow-up, based on National Death Index data. During follow-up (median time: 176 months), 1280 subjects died, 503 of them from CVD. Adults reporting eating ≥6 times/day had a lower hazard ratio for CVD mortality than those reporting eating 4 times/day (hazard ratio = 0.68; 95% confidence interval, 0.43–1.08; test for trend, P = .011). The gradient of CVD mortality risk by eating frequency was significant for the groups with ≥2500 kcal of total energy intake (test for trend, P = .037). Eating frequency was inversely associated with CVD mortality, which was especially marked for people reporting high total energy intake. Nevertheless, public health recommendations should be cautious, as eating frequency was positively associated with total energy intake, which could promote weight gain.